Camilla and the Dresses - Ferenczi, Attila (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
This article aims to create a context around a single line of the Aeneid. The narrator's statement narrating Camilla's death (femineo predae et spoliorum ardebat amore 11,782) is traditionally understood as prejudiced against women and does not quite fit with the earlier portrayal of Camilla's figure. The paper will argue that, on the one hand, the interpretation of the line is not as clear-cut as it may seem at first sight, and on the other hand, that the motivation attributed to Camilla by this statement contains an element that is quite unique in the Aeneid, and is characterised by ambivalence of values rather than by a clear rejection of her morality. The analysis tries to interpret the whole sentence through the nature of the spoils (praeda) mentioned in the sentence. By comparing Camilla's appearance and the clothing of her opponents in battle, it seeks to formulate connections between the different characters in the story.